CORPORATE GOVERNANCE BASED ON POJK NO. 17/2023, DIGITAL MATURITY, AND FIRM VALUE: THE MEDIATING ROLE OF ESG PERFORMANCE IN BANKING COMPANIES LISTED ON THE IDX - Haninun Haninun; Septa Cahya Dinia; Khairudin Khairudin (PT. Saha Kreasi Indonesia, 2026)
This study investigates the effects of governance implementation based on POJK No.17/POJK.03/2023 and digital maturity on firm value, with Environmental, Social, and Governance (ESG) performance serving as a mediating variable among banking companies listed on the Indonesia Stock Exchange during 2024–2025. The study is motivated by the condition in which the banking industry maintained relatively strong fundamental performance while experiencing pressure in market valuation, indicating the growing importance of non-financial factors in shaping investors’ perceptions. A quantitative approach was employed using secondary data obtained from annual reports, sustainability reports, financial statements, and market data. The sample was selected using purposive sampling, resulting in 30 banking companies and 60 firm-year observations over the two-year observation period. Governance implementation, digital maturity, and ESG performance were measured using content analysis based on a disclosure index, while firm value was proxied by Tobin’s Q. The data were analyzed using panel data regression with EViews 13, including model selection, classical assumption testing, partial and simultaneous significance tests, coefficient of determination, and the Sobel test to examine the mediating effects. The findings demonstrate that governance implementation based on POJK No.17/POJK.03/2023 and digital maturity have positive and significant effects on both firm value and ESG performance. ESG performance also has a positive and significant effect on firm value. Furthermore, ESG performance significantly mediates the effects of governance implementation and digital maturity on firm value. The model indicates that governance implementation and digital maturity explain 88.81% of the variation in ESG performance, while governance implementation, digital maturity, and ESG performance jointly explain 94.42% of the variation in firm value. These findings highlight the importance of integrating corporate governance, digital transformation, and sustainability into banking management strategies to strengthen stakeholder confidence and enhance firm value.